Managers' experience-based understanding of capacity to work in workers with common mental disorders. (20th October 2021) - Tengelin, E; Hensing, G; Holmgren, K; Ståhl, C; Bertilsson, M
Abstract: Background: The capacity to work among workers with common mental disorders (CMD) is important to understand but scarcely explored from a manager perspective, even though their views could add essential knowledge. The aim of this study was to explore and describe managers' experience-based understanding of capacity to work in individuals with CMD. Methods: This qualitative focus group study used inductive manifest content analysis as analytic technique. First-line managers with experiences of employees with CMDs were recruited via organizations and networks. Eight focus group interviews with altogether 31 participants were performed. Results: The analysis resulted in five categories of managers' experience-based understanding of occupational functioning in workers with CMDs: (1) The capacity to mentally focus on work tasks decreases or disappears, with negative consequences for work output. (2) The capacity to commit to continuous and coherent tasks changes, making tasks that span over longer periods of time difficult. (3) The capacity to independently adapt to the needs of the situation decreases, causing the worker to need more guidance and instructions than usual. (4) The capacity to keep up professional appearances is reduced, meaning that the worker struggle with the professional role. Finally, (5) the ability to interact socially and professionally decreases, which potentially causes conflicts at the workplace. Conclusions: This study shows managers' experience-based understanding of CMDs in workers as severe changes and reductions of employees' capacities needed for occupational functioning. These findings add to the understanding of the construction of the capacity at the workplace. A deeper understanding of reduced work capacity is also needed to adapt workplaces and our findings can facilitate work accommodations for employees with CMDs. Key messages: This study adds a manager perspective to the increasing knowledge about how capacity to work is influenced by CMD. This study shows that managers experience that CMD in workers severely change and reduce employees' capacities needed for occupational functioning.